Pain and pain mechanisms in patients with inflammatory arthritis: A Danish nationwide cross-sectional DANBIO registry survey - Rifbjerg-Madsen, S. (PLoS One, 2017)
BACKGROUND: Central pain mechanisms may be prominent in subsets of patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and other spondyloarthritis (SpA). The painDETECT questionnaire (PDQ) identifies neuropathic pain features, which may act as a proxy for centrally mediated pain. The objectives were to quantify and characterize pain phenotypes (non-neuropathic vs. neuropathic features) among Danish arthritis patients using the PDQ, and to assess the association with on-going inflammation. METHODS: The PDQ was included onto the DANBIO touch screens at 22 departments of Rheumatology in Denmark for six months. Clinical data and patient reported outcomes were obtained from DANBIO. A PDQ-score >18 indicated neuropathic pain features, 13–18 unclear pain mechanism and <13 non-neuropathic pain. RESULTS: Pain data (visual analogue scale, VAS) was available for 15,978 patients. 7,054 patients completed the PDQ (RA: 3,826, PsA: 1,180, SpA: 1,093). 52% of all patients and 63% of PDQ-completers had VAS pain score ≥ 30 mm. The distribution of the PDQ classification-groups (<13/ 13-18/ >18) were; RA: 56%/24%/20%. PsA: 45%/ 27%/ 28%. SpA: 55% / 24%/ 21%. More patients with PsA had PDQ score >18 compared to RA and SpA (p<0.001). For PDQ > 18 significantly higher scores were found for all patient reported outcomes and disease activity scores. No clinical difference in CRP or swollen joint count was found. Logistic regression showed increased odds for having VAS pain ≥39 mm (the median) for a PDQ-score >18 compared to <13 (OR = 10.4; 95%CI 8.6–12.5). CONCLUSIONS: More than 50% of the Danish arthritis patients reported clinically significant pain. More than 20% of the PDQ-completers had indication of neuropathic pain features, which was related to a high pain-level. PDQ-score was associated with DAS28-CRP and VAS pain but not with indicators of peripheral inflammation (CRP and SJC). Thus, pain classification by PDQ may assist in mechanism-based pain treatment.